2018
DOI: 10.1016/j.kint.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Executive summary of the 2018 KDIGO Hepatitis C in CKD Guideline: welcoming advances in evaluation and management

Abstract: g u i d e l i n e s u m m a r y Kidney International (2018) 94, 663-673 Algorithm 1 | Treatment scheme for chronic kidney disease (CKD) G1 to G5D. (See Algorithm 2 for kidney transplant recipients.) Recommendation grades (1À2) and strength of evidence (AÀD) are provided for each recommended treatment regimen and hepatitis C virus (HCV) genotype; see full guideline. 1 DAA, direct-acting antiviral; GFR, glomerular filtration rate; NAT, nucleic acid testing. M Jadoul et al.: Summary of 2018 KDIGO HCV in CKD Guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 6 publications
2
68
0
2
Order By: Relevance
“…Hepatitis C virus (HCV) affects over 70 million people worldwide, corresponding to 1.0% of the global population [1]. Public interest in HCV is growing, especially since the virus can also induce extrahepatic manifestations (in 40-70% of cases) including autoimmunity-related symptoms, metabolic, renal, cardiovascular, central nervous system or lymphoproliferative disorders [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) affects over 70 million people worldwide, corresponding to 1.0% of the global population [1]. Public interest in HCV is growing, especially since the virus can also induce extrahepatic manifestations (in 40-70% of cases) including autoimmunity-related symptoms, metabolic, renal, cardiovascular, central nervous system or lymphoproliferative disorders [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…But, HCV treatment in HD patients is not endorsed as a strategy to prevent HCV transmission within HD units. 4 However, for individual patients there may be a number of other considerations mainly related to potential renal transplantation candidacy and use of organs from HCV seropositive donors. HCV transmission can occur from HCV viremic donors to recipients.…”
Section: Consequences Of Hcv Infection For An Individual Patient Not mentioning
confidence: 99%
“…A series of studies have confirmed that HCV transmission on HD reflects lack of adherence to these precautions . In contrast to the prevention of hepatitis B transmission in this setting, dedicated dialysis machines for HCV‐infected patients are not recommended . The likelihood of HCV acquisition while on HD is increased in units with a higher background prevalence of HCV infection, so an infected HD patient also places others at risk.…”
mentioning
confidence: 99%
See 2 more Smart Citations